COVID-19＆depression: New and detailed evidence from NHANES - Hongxuan Fan; Zhaoyu Ren; Ping Zhang; Boda Zhou (Journal of Infection and Public Health)
This study aimed to investigate the changes in depression prevalence among American adults following the COVID-19 pandemic. A cross-sectional study design was employed. Data were acquired from three cycles of the National Health and Nutrition Examination Survey (NHANES) spanning from 2017 to 2023. The 2017–2020 cycles were classified as pre-pandemic by the National Center for Health Statistics, while the 2021–2023 cycle was regarded as pandemic and post-pandemic. Adult participants aged 20 years and older with complete data from the PHQ-9 assessment were included. The prevalence of depression among American adults increased from 8.45 % pre-pandemic to 12.20 % during and after the pandemic. Stratified by age, the prevalence of depression was significantly higher during and after the pandemic compared to pre-pandemic period in 20–39 years (Prevalence: 16.56 %, P < 0.0001). Following the pandemic, the prevalence of depression among American adults has significantly increased. The most significant increase was observed in the younger age group of 20–39 years.